Sistem Pendukung Keputusan Penjualan Barang Impor Menggunakan Metode Benefit Cost Ratio - Louis Kelwin; Erick Dazki (G-Tech: Jurnal Teknologi Terapan, 2023)
Trade is one of the many activities carried out by humans. One of the goods that is often used for trading activities is imported goods. It can be seen that the sale of imported goods is one of the many activities carried out by the people of Indonesia. The main reason for selling imported goods is the relatively large profit level if choosing the right goods. By using a decision support system that uses the Benefit Cost Ratio method, users can determine which goods are suitable for import and resale. There are several main factors used to determine the goods to be imported, namely price of the goods, quantity of goods, total price for sending the goods, marketing price and selling price of the goods. The results of the system implementation show that the decision support system application using the BCR method can determine the appropriate goods for import and resale.